Implementasi Strategi Brand Image Lembaga untuk Meningkatkan Mutu Pendidikan - Romadhon, Firman; Abdurrahman, Abdurrahman (Universitas Nurul Jadid, 2023)
Efforts to develop Islamic educational institutions are a necessity in the context of recent global economic developments and signal the importance of increasing the independence and competitiveness of a country in the international world. The purpose of this study is to analyze the implementation of brand image in the Zaid Bin Tsabit area of Nurul Jadid Islamic Boarding School. The research method used is qualitative research with a descriptive type with an interview approach, documentation and in-depth observation. The results of this study indicate that the brand image that applies in the Zaid bin Tsabit environment can make people choose and be interested in placing their students so that what is expected can be achieved.